1979
DOI: 10.1071/ea9790023
|View full text |Cite
|
Sign up to set email alerts
|

Supplementation of sheep grazing wheat stubble with urea, molasses and minerals: quality of diet, intake of supplements and animal response

Abstract: Supplements of urea, molasses and minerals were offered for 15 weeks to mature crossbred wethers grazing wheat stubble at Condobolin in central New South Wales. The sheep were then grazed without supplements on a phalaris-subterranean clover pasture for a further five weeks. On the wheat stubble, dead crop residues amounted to more than 4000 kg DM ha-1 and constituted 95% or more of the available plant material throughout the experiment. Diets selected by the sheep contained significant amounts of grain or gre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

1990
1990
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 7 publications
1
6
0
Order By: Relevance
“…Liveweight differences between supplemented and control ewes declined during lactation (Figure 3). This observation supports the idea that the initial differences caused by undernutrition may disappear following a period of high levels of nutrition, outweighing the benefits of previous supplementation (Entwistle and Knights, 1974;Mulholland and Coombe, 1979). This hypothesis may be valid at an individual level, but not at a population level, because, even though the positive effect of supplement on ewe and lamb live weight was not sustained, its influence on total lamb production will persist.…”
Section: Figuresupporting
confidence: 78%
See 1 more Smart Citation
“…Liveweight differences between supplemented and control ewes declined during lactation (Figure 3). This observation supports the idea that the initial differences caused by undernutrition may disappear following a period of high levels of nutrition, outweighing the benefits of previous supplementation (Entwistle and Knights, 1974;Mulholland and Coombe, 1979). This hypothesis may be valid at an individual level, but not at a population level, because, even though the positive effect of supplement on ewe and lamb live weight was not sustained, its influence on total lamb production will persist.…”
Section: Figuresupporting
confidence: 78%
“…Several experiments around the world suggest a clear effect of supplementation on the performance of pen-fed sheep; however, responses in the field have been less clear (Tudor and Morris, 1971;Mulholland and Coombe, 1979;Butler et al, 1987). This discrepancy may arise from several causes: (1) diet selectivity is more important in field experiments (Tudor and Morris, 1971), (2) diet selection may change with supplementation (Hatfield et al, 1991), (3) urea often decreases forage palatability (Bhattacharya and Pervez, 1973;Butler et al, 1987), (4) unsupplemented sheep may show compensatory growth in the more favourable season (Entwistle and Knights, 1974;Mulholland and Coombe, 1979) and (5) N-restricted sheep may markedly increase their nitrogen use efficiency by reducing nitrogen excretion and increasing N recycling (Farid, 1985;Farid et al, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…However, if individual animal supplement consumption is measured, and there are three animals that consume no supplement, and two animals that consume .5 kg/d, then only 50% of the animals consumed at least the target amount. Mulhol-land and Coombe (1979) used disappearance of supplement to estimate intake and found this method resulted in 100% of target intake by grazing wethers for molasses and molasses-urea liquid supplements, whereas only 55 and 40% of sheep consumed the target amount or more of molasses and molasses-urea liquid supplements, respectively, when individual supplement consumption was measured.…”
Section: Supplement Type and Delivery Methodsmentioning
confidence: 99%
“…Individual supplement intake measured using tritiated water indicated that the proportion of nonfeeders was 49%, and the CV for individual supplement intake was 52%. Mulholland and Coombe (1979) offered crossbred wethers grazing wheat crop residue access to molasses-based mineral or mineral-urea block supplements, or to molasses or molasses-urea liquid supplements in roller lick troughs. Mean supplement intake as a percentage of the target intake was 11% for the mineral block, 28% for the molasses-urea block, 55% for the molasses, and 37% for the molasses-urea liquid supplement.…”
Section: Supplement Form Liquid and Block Supplementsmentioning
confidence: 99%
“…ASUMMB provides all essential nutrients . However, Mulholland and Coombe (1979) have found no improvement in wool production on urea molasses mineral block supplementation in sheep.…”
Section: Advances In Animal Andmentioning
confidence: 99%